2014
DOI: 10.1039/c4ay01113a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, optimization and application of poly(ethylene glycol)methyl ether methacrylate/urethane methacrylate as a new polar phase for stir bar sorptive extraction

Abstract: The aim of this paper is to discuss the determination of carbaryl in a water sample using a stir bar sorptive extraction method based on a new polar extraction phase coupled with HPLC-DAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Due to hydrophobic nature of PDMS‐based stir bars, there was a limitation on the application of polar compound extraction. In recent years, there has been a growing interest in development of new commercial stir bars and in‐house coatings for SBSE to improve their polarity, selectivity, and stability . Several SBSE‐related reviews have been reported, mainly focusing on preparation of different coatings .…”
Section: Introductionmentioning
confidence: 99%
“…Due to hydrophobic nature of PDMS‐based stir bars, there was a limitation on the application of polar compound extraction. In recent years, there has been a growing interest in development of new commercial stir bars and in‐house coatings for SBSE to improve their polarity, selectivity, and stability . Several SBSE‐related reviews have been reported, mainly focusing on preparation of different coatings .…”
Section: Introductionmentioning
confidence: 99%